Pious passion : the emergence of modern fundamentalism in the United States and Iran - Riesebrodt, Martin (Comparative studies in religion and society, 1993)
Martin Riesebrodt's unconventional study provides an extraordinary look at religious fundamentalism. Comparing two seemingly disparate movements-in early twentieth-century United States and 1960s and 1970s Iran-he examines why these movements arose and de.